Utilizing Instagram for Tourism Package Marketing in the Pandemic Era CV Nara Tour Organizer - Nopita, Dewi; Muin, Rezi Edi (Jurnal Internasional Bisnis, Humaniora, Pendidikan dan Ilmu Sosial, 2023)
The travel agency is one of the business ventures with great potential and is growing rapidly coupled with technological advances. CV Nara Tour Organizer is present as one of the travel agencies domiciled in Yogyakarta. In its development, it experienced various competition between fellow travel agencies. In addition to intense competition, entering 2020, the world is shaken by the Covid 19 or Corona outbreak, which is detrimental to all aspects of life, especially the travel business sector. CV Nara Tour Organizer is one of the companies affected. With the influence of digital marketing, it is hoped that the company will survive and compete in the future, even in this pandemic. This type of research is descriptive with a qualitative approach. The study was conducted using the research subject's CV Nara Tour Organizer located in the Province of the Special Region of Yogyakarta. This data collection uses in-depth interviews, observations, and documents. The data analysis used is to collect, reduce, present, and conclude. The results of this study indicate the influence of digital marketing on progress in marketing the travel agency CV Nara Tour Organizer in this pandemic era.